Doppler flow characteristics in the assessment of pulmonary artery pressure in ductus arteriosus. Issue 4 (October 1989) - Houston, A B; Lim, M K; Doig, W B; Gnanapragasam, J; Coleman, E N; Jamieson, M P; Pollock, J C
Abstract : The Doppler spectral pattern of flow through the ductus arteriosus was studied in 117 patients. In 37 who underwent catheterisation, Doppler records and aortic and pulmonary artery pressure were available (21 simultaneously with two catheters) for review while the others had surgical ligation of the duct on the basis of the results of non-invasive tests. Four flow patterns were obtained: (a) continuous flow, maximum velocity in late systole with gradual fall throughout diastole; (b) continuous flow, high systolic flow with rapid fall to a very low early diastolic velocity maintained throughout diastole; (c) continuous low velocity, maximum in late diastole; and (d) bidirectional flow. Flow pattern (a) was associated with normal or slightly raised pulmonary artery pressure; (b) with raised pulmonary artery pressure; and (c) and (d) with pulmonary artery pressure at systemic values. Comparison of the Doppler and measured pressure differences between the great arteries was reasonably good for peak values but poor for the trough readings. Doppler ultrasound clearly showed ductal flow; the flow pattern gave an indication of the pulmonary artery pressure, but pressure measurement by application of the Bernoulli equation to the flow velocities cannot yet be regarded as reliable.